2013
DOI: 10.9790/3013-034204853
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects Of Melatonin on Leptin, Testosterone and Biochemical Parameters in Albino Rats

Abstract: : The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The data of the present study indicated that in shamoperated surgery and PINx rats leads to regressive histological changes in testicular tissue. This result is supported by Mahmud and Mahmud, finding that male albino rats were given MEL 60 mg / kg diet and MEL 120 mg / kg, the level of testosterone was significantly decreased in ratio 30% and 60% respectively [16]. Furthermore, Masson-Pevet et al, (1987) [17], found that MEL play protective role in gonads, and they showed that exposure of hamster to short photoperiod leads to regression of testicular tissue.…”
Section: Tikrit Journal Of Pure Science 22 (9) 2017 Issn: 1813 -1662 ...mentioning
confidence: 65%
“…The data of the present study indicated that in shamoperated surgery and PINx rats leads to regressive histological changes in testicular tissue. This result is supported by Mahmud and Mahmud, finding that male albino rats were given MEL 60 mg / kg diet and MEL 120 mg / kg, the level of testosterone was significantly decreased in ratio 30% and 60% respectively [16]. Furthermore, Masson-Pevet et al, (1987) [17], found that MEL play protective role in gonads, and they showed that exposure of hamster to short photoperiod leads to regression of testicular tissue.…”
Section: Tikrit Journal Of Pure Science 22 (9) 2017 Issn: 1813 -1662 ...mentioning
confidence: 65%